Juridical Study of Judges' Considerations in Deciding Pretrial Applications - Laiya, Moh Hamdi; Darmawati, Darmawati; Insani, Nur (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
The purpose of this study was to analyze the evidentiary testing system through pretrial for the crime of child intercourse, as well as to find out and analyze the basic considerations of the judge in deciding the pretrial request for the crime of child intercourse. This research used normative legal research method which were carried out by studying theories, concepts, views and legal norms related to this research as well, empirical research was carried out by approaching facts and existing phenomena. The results of this study indicated that in testing pretrial evidence, negative statutory evidence can be called negative wettelijk. determining a suspect was obtained at the investigation stage by considering the nature of the results of the post mortem et repertum, the judge can use this evidence as one of the pieces of evidence to designate someone as a suspect. As for the recommendation that law enforcement officers, especially judges, in making decisions, must be guided by the Criminal Procedure Code and the Constitutional Court Decision Number 21/PUU-XII/2014